(untitled) (Global Journal of Human-Social Science, 2015)
This paper explores development and functioning of Indigenous education systems of Canada and the Russian Federation. Reconstructing educational phenomena on the basis of qualitative data, the author builds historical models of education systems in both countries, presents their structures, contents and basic components. Recognizing secondary schooling as an integral component of each system, the author investigates such issues as boarding schools, language in education, and the issue of teaching staff. In order to assess boarding school educational effectiveness, the author explores pedagogical process and indicates its interior controversy which may stipulate various weaknesses specified for boarding schools. Comparing experiences of language using in both education systems, the author indicates and analyzes a number of benefits and weaknesses of each experience. In connection with this, bilingual education benefits are considered. In addition, various forms of teacher training are presented and a number of their weaknesses are indicated.